Assessment of Women Participation in Rice Processing Value Chain in Cross River State, Nigeria - Effiong, John Ben (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2025)
This study assessed women’s participation in the rice processing value chain and identified the constraints limiting their engagement in Cross River State, Nigeria. Conducted across the three agricultural zones of the state, the research adopted a multi-stage sampling technique to select 284 women actively involved in rice value chain activities. Data were collected using a semi-structured questionnaire and analyzed using descriptive and inferential statistics, including frequencies, percentages, means, and rankings. The findings revealed that women played a significant role in all stages of rice processing, particularly in parboiling, drying, milling, and bagging, with over 80% involvement across these activities. Most of the women (97.3%) used locally fabricated machines, while only 2.7% had access to industrial machines, which were largely privately owned, reflecting limited accessibility due to high costs. Constraints identified included high cost of fuel (mean = 4.754) and epileptic power supply (mean = 4.567), both of which significantly hinder effective processing. These challenges, if not addressed, may undermine women's productivity and economic empowerment in the rice value chain. The study concluded that woman in Cross River State are highly active in rice processing value chain activities, particularly in parboiling, drying, milling, and bagging. The study recommends targeted interventions such as subsidized access to processing equipment, stable electricity supply, and enhanced support services to strengthen women’s participation in the sector.